Status rodzinny i nieformalne nierodzinne sieci wsparcia a zamieszkiwanie w instytucjach opiekuńczych - Szweda-Lewandowska, Zofia (Studia Demograficzne, 2014)
The majority of countries, including Poland, face a phenomenon of population ageing. Therefore, providing care for elderly persons becomes a crucial challenge for the societies. A decline in the care-giving potential of families and the rapid increase of numbers of seniors create a need for development of institutional assistance for the elderly. The population of seniors is heterogeneous. Thus, there are different reasons for providing public assistance, and different paths of accessing institutional assistance. The aim of the article is to present the family status of seniors, who wait for a place in a residential care, and their non-familial, informal support networks. To achieve this objective we conduct a survey among 221 social workers who assist seniors and their families through the admittance process for residential care in Łódź – a city with advanced ageing (22.3% of people aged 60+).